Real Time Train Monitoring using Google Maps - Supeno Djanali; Ary M. Shiddiqi; Hudan Studiawan; Henning T. Ciptaningtyas (IPTEK Journal of Proceedings Series, 2014)
Recently, there are many train accidents occurred in Indonesia where train collision contributes most of the causes. PT Kereta Api Indonesia (KAI) as state-owned enterprise that is responsible in monitoring train movement has not implemented a real time monitoring system. Thus, the current monitoring system relies on radio communication between train stations and train driver. In this paper, we propose a system to assist PT KAI to monitor train activities in a real time fashion. The system is implemented on a web based application. This web-based monitoring application equipped with complete station and train data in Java and Sumatra Islands. All trains latitude and longitude positions are retrieved through an embedded GPS device on train and the longitude and latitude data are then submitted to database server. At the server, the data is displayed in Google Maps accessible to authorized users. With this real time train monitoring system, PT KAI can track all train positions simultaneously. Therefore, the operating trains can be notified should a train collision potential is detected. Thus, the safety of rail passengers will be more assured.